2019
DOI: 10.1101/796870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human CardioChimeras: Creation of a Novel ‘Next Generation’ Cardiac Cell

Abstract: Background: CardioChimeras (CCs) produced by fusion of murine c-kit + cardiac interstitial cells (cCIC) with mesenchymal stem cells (MSCs) promote superior structural and functional recovery in a mouse model of myocardial infarction (MI) compared to either precursor cell alone or in combination. Creation of human CardioChimeras (hCC) represents the next step in translational development of this novel cell type, but new challenges arise when working with cCICs isolated and expanded from human heart tissue sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Recent work has boldly attempted to create "enhanced" engineered cells derived from hCICs and/or hMSCs (Mohsin et al, 2012;Quijada et al, 2015;Broughton et al, 2019;Firouzi et al, 2020). For example, Quijada et al showed that fused hCIC-hMSC CardioChimeras were superior to hCICs alone, hMSCs alone, or their combination in a single suspension (Quijada et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has boldly attempted to create "enhanced" engineered cells derived from hCICs and/or hMSCs (Mohsin et al, 2012;Quijada et al, 2015;Broughton et al, 2019;Firouzi et al, 2020). For example, Quijada et al showed that fused hCIC-hMSC CardioChimeras were superior to hCICs alone, hMSCs alone, or their combination in a single suspension (Quijada et al, 2015).…”
Section: Introductionmentioning
confidence: 99%